The impact of job crafting on job engagement with meaningfulness of work as a mediating variable: A research in Indonesia and India - Violinda, Qristin; Setyorini, Noni; Nugraha, Aryan Eka Prasetya; Noorzeha, Fuad; Som, Sanchita (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
Classic job design theory has evolved over a long period. It focuses on employees' ability to autonomously modify their job characteristics; however, tools for assessing the dimensions of job crafting remain limited. The goal of this study is to determine how job engagement, job crafting, and meaningfulness of work are related. The partial least squares (PLS) 3.0 analysis tool was used in the path analysis. Data were obtained through an online questionnaire using the Job Crafting Questionnaire, the Dutch Utrecht Work Engagement Scale, and the MLQ Questionnaire. The purposive sampling technique was used to identify 204 respondents working in private and public companies. The results demonstrate that in Indonesia and India, task crafting, and cognitive crafting have a positive and significant relationship with the meaningfulness of work. In turn, this mediates the influence of relational crafting on job engagement for Indonesian subjects (β= 0.111, sig= .019) but not for Indian ones (β = 0.054, sig = .455). It is hoped that the study will contribute to the implementation of programs for human resource development related to job crafting design to improve performance effectiveness.